Fabrication and characteristics of a 4H-SiC junction barrier Schottky diode - 陈丰平 张玉明 吕红亮 张义门 郭辉 郭鑫 (Journal of semiconductors, 2011)
4H-SiC junction barrier Schottky（JBS）diodes with four kinds of design have been fabricated and characterized using two different processes in which one is fabricated by making the P-type ohmic contact of the anode independently,and the other is processed by depositing a Schottky metal multi-layer on the whole anode.The reverse performances are compared to find the influences of these factors.The results show that JBS diodes with field guard rings have a lower reverse current density and a higher breakdown voltage,and with independent P-type ohmic contact manufacturing,the reverse performance of 4H-SiC JBS diodes can be improved effectively. Furthermore,the P-type ohmic contact is studied in this work.